A review on heat transfer in heat exchanger - P. Jayapradha; Arun Prakash J (AG Volumes, 2022)
In today’s society, conserving energy is of paramount importance, and a heat exchanger is a great tool for doing just that. When it comes to processes like distillation, dissolution, crystallisation, fermentation, etc., a heat exchanger is obviously the most crucial part of the apparatus. Therefore, it is crucial in these process sectors to choose the right heat exchanger. Due to its small size and effective heat transmission, spiral heat exchangers have earned a stellar reputation. Since the fluids are moving in opposite directions, the heat exchanger may bring the temperatures of the two media it’s working with quite near together. Spiral heat exchangers may be useful for a wide variety of fluids, including those that include particles or fibres, slurries, mixes with inert gases, waste water, cooling and heat recovery fluids, vapour/liquid condenser fluids, and vacuum condenser fluids with inert gases.